Prediksi Laju Respirasi Terong dengan Persamaan Arrhenius - Maya Sari; Juliana Simbolon (Universitas Quality, 2020)
North Sumatera is the third largest producer of eggplant, therefore, postharvest handling of eggplants needs to be done, precooling, to maintain physic quality of eggplant from farming to consumer. Temperature is the one of main factor to effect respiration rate and change in physical quality of eggplants. Precooling and cold storage is applied. Predicting of respiration rate based on Arrhenius Equation. Result research showed that high score activation energy is precooling 10 minute, precooling 20 minute, and the lower score is non precooling. The best combination of treatments eggplant is precooling and then cold storage.